Growth Pattern of the Tropical Highland Gymnopthalmid Lizard iAnadia Bogotensis/i in Captivity Conditions (2018)
We estimated growth pattern and growth rate of individuals of Anadia bogotensis in captivity and under climatic conditions similar to those in the wild. We collected eggs of this species from communal nests from a highland locality in the municipality of La Calera, Cundinamarca, in Colombia. The eggs were incubated in outdoors terrariums, and the growth of the hatchlings was recorded until their death. The growth pattern fits a logistic model, in which individuals grow moderately at the beginning, and then their growth rate increases. The growth rate increases even after individuals reach sexual maturity and seems to decrease close to their maximum body size. It is a fast growing species that reaches sexual maturity at around 50 % of its maximum body size and has a lifespan of less than two years. This strategy could be a consequence of high predation pressures, but it is a hypothesis that needs to be tested in the wild, highland Andes.